Low frequency Raman study of interlayer couplings in WS2–MoS2 van der Waals heterostructures. (3rd June 2020) - Saito, Yuika; Kondo, Takahiro; Ito, Hiroki; Okada, Mitsuhiro; Shimizu, Tetsuo; Kubo, Toshitaka; Kitaura, Ryo
Abstract: Interlayer coupling in WS2 –MoS2 van der Waals heterostructures was studied using low-frequency resonance Raman spectroscopy. The relationship between high-frequency Raman modes and a low-frequency Raman mode were investigated. The Raman intensity of interlayer shear-mode exhibited a linear correlation with the intensity of the two modes A1g and E2g 1 . The frequency difference between these two modes, A1g −E2g 1, was also investigated. Microscopic measurements showed that the intensity ratio A1g /E2g 1 is sensitively modulated by the spatially non-uniform electronic potential. On the other hand, A1g −E2g 1 is stable and is determined by the number of layers and layer stacking configurations. Therefore, both parameters can be used independently to discuss the quality of vdW heterostructures. Our findings provide convenient markers for studying interlayer coupling of vdW heterostructures using Raman spectroscopy.